True detective. The complete third season [videorecording (DVD)] - Pizzolatto, Nic, 1975-; Ali, Mahershala, 1974-; Dorff, Stephen, 1973-; Ejogo, Carmen, 1974- (HBO Home Entertainment, 2019)
The critically acclaimed anthology series returns for its third season, this time starring Oscar winner Mahershala Ali and Stephen Dorff.